Four new species of the digger wasp genus Ammophila W. Kirby, 1798 (Hymenoptera, Sphecidae) from Central Asia - Danilov, Yuriy N. (Zootaxa, 2018)
Four new species of Ammophila from Central Asia are described and illustrated: A. antoninae (Tajikistan), A. kondarensis (Tajikistan), A. nemkovi (Uzbekistan), and A. yaroslavi (Kazakhstan, Turkmenistan).